Six-Year Bond Stability of Universal Adhesives with Alternative Dentin Treatments. (2022) - Rodrigues, R.V.; Al-Mosuli, T.; Carvalho, R.M.; Manso, A.P.
Abstract : Purpose/Aim: Evaluate the effects of four dentin treatments on microtensile bond strength (MBS) for two universal adhesives, ScotchBond Universal (SBU) and All-Bond Universal (ABU), after 24-hour, 1-year and 6-year water storage. Materials and Methods: Flat dentin surfaces from human molars were treated as follows: (i) phosphoric acid 35% (PA) for 15 s; (ii) PA for 5 s; (iii) 17% EDTA for 60 s; (iv) no treatment (self-etch mode). One of the two universal adhesives was then applied to the surface. After 24-hour storage at 37 C, teeth were sectioned to obtain beams (~0.9mm2) and randomly assigned to one of the storage times (24 h, 1-y and 6-y). Specimens were tested until failure at 1.0 mm/min on each incubation period. Failure modes were assessed with light microscope at 40x (Olympus, Tokyo, Japan). Data was submitted to Three-Way ANOVA and all pairwise multiple comparison (Holm-Sidak) at significance level = 0.05. Results: Statistical differences were detected for surface treatments and storage times. A significant interaction between adhesive and treatment was found (p<0.01). The bond strengths were affected by the different surface treatments, depending on the adhesive, except for 17% EDTA with similar results for both systems. After 6-year storage, SBU showed more stable MTBS with 17% EDTA 32.36 (14.09) and self-etch mode 30.10 (13.80) (p<0.05). For ABU, the lowest MTBS was observed with the self-etch mode for all storage times (p<0.01). However, 17% EDTA treatment for ABU at 6-year storage 39.85 (21.03) exhibited the highest MTBS (p<0.01). Overall, 17% EDTA treatment showed a positive effect on dentin bonding stability. The self-etch mode showed better performance for SBU compared to ABU. The failure modes for all groups were predominantly adhesive and mixed. Conclusions: The dentin bonding stability with universal adhesives depends on the surface treatment for each adhesive material. The use of 17% EDTA for 60 s to treat dentin prior to the application of universal adhesives could be considered an alternative approach to improve bond durability.